Information systems for health sector monitoring in Papua New Guinea - Cibulskis R.E.; Hiawalyer G. (Bulletin of the World Health Organization, 2002)
This paper describes (i) how a national health information System was designed, tested and implemented in Papua New Guinea, (ii) how the system was integrated with other management information systems, and (iii) how information has been used to support decision-making. It concludes that central coordination of systems design is essential to make sure that information systems are aligned with government priorities and can deliver the information required by managers. While there is often scope for improving the performance of existing information systems, too much emphasis can be placed on revising data collection procedures and creating the perfect information system. Data analysis, even from imperfect systems, can stimulate greater interest in information, which can improve the quality and completeness of reporting and encourage a more methodical approach to planning and monitoring services. Our experience suggests that senior decision-makers and political leaders can play an important role in creating a culture of information use. By demanding health information, using it to formulate policy, and disseminating it through the channels open to them, they can exert greater influence in negotiations with donors and other government departments, encourage a more rational approach to decision-making that will improve the operation of health services, and stimulate greater use of information at lower levels of the health system. The ability of information systems to deliver these benefits is critical to their sustainability.